Simplifying MATCH WORD: Evidence from English functional categories. Issue 1 (29th January 2019) - Tyler, Matthew
Abstract : In work on the syntax-prosody interface, there is a prevalent idea that while lexical categories are preferentially mapped to prosodic words, no such pressure exists for functional categories (Selkirk 1984 ; 1996 ; 2011 ; Selkirk & Shen 1990 ; Truckenbrodt 1999 ; Elfner 2012 ). In Match Theory (Selkirk 2011 ), in which syntax-prosody isomorphism is enforced by a series of violable constraints, this supposed pressure is built into the system with the claim that MATCH WORD in some sense "ignores" functional categories. I argue that this idea is misguided, and that MATCH WORD does not discriminate between lexical and functional heads. The pervasive phonological reduction of function words is instead ascribed to the idiosyncratic prosodic requirements of the function words themselves. In particular, I adopt the model of Prosodic Subcategorization (Inkelas 1989 ; Zec 2005 ). This approach explains particular interactions that would be unexpected if MATCH WORD were genuinely indifferent to functional categories, and fits in with a large body of evidence suggesting that functional elements can behave in prosodically idiosyncratic ways (Nespor & Vogel 1986 ; Inkelas & Zec 1990 ; Zec 2005 ). The evidence comes from the behavior of several classes of English functional categories: prepositions, auxiliaries, determiners, weak object pronouns and contracted negation - n't .